The Construction of Masculinity Reflected through Fashion in The Wild One (1953) Film - Sulistiawan, Tegar Aliyyu (JETLEE: Journal of English Language Teaching, Linguistics, and Literature, 2024)
This article seeks to explore the traits of the characters in The Wild One film as well as the construction of masculinity reflected through dress or costumes in the film. The findings of this study reveal that there is a symbol in The Wild One that has a sense of masculinity based on the Greasers' outfit. The author implies the traits of the characters and the concept of masculinity established via the fashion of the Greasers in the film The Wild One, in which masculine men like the Greasers are emblems of world masculinity. They must have a well-built, strong body and an attractive appearance, and they must always appear daring and brave. All of these criteria are concepts owned by the Greasers culture. According to the findings of this study, the construction of masculinity in popular culture refers to the Greasers' concept of masculinity. The presence of a hidden message in the film The Wild One, where the attire of the Greasers, who embody the image of masculinity in the modern period, produces the concept of consumerism and materialism, was also discovered.